2016
DOI: 10.1016/j.msec.2016.05.086
|View full text |Cite
|
Sign up to set email alerts
|

Determining iron oxide nanoparticle heating efficiency and elucidating local nanoparticle temperature for application in agarose gel-based tumor model

Abstract: Magnetic iron oxide nanoparticles (MNPs) have been developed for magnetic fluid hyperthermia (MFH) cancer therapy, where cancer cells are treated through the heat generated by application of a high frequency magnetic field. This heat has also been proposed as a mechanism to trigger release of chemotherapy agents. In each of these cases, MNPs with optimal heating performance can be used to maximize therapeutic effect while minimizing the required dosage of MNPs. In this study, the heating efficiencies (or speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 62 publications
(102 reference statements)
4
14
1
Order By: Relevance
“…4 b). A similar 50% decrease in SAR was also reported by Makridis et al 18 and Shah et al 41 for ferrite-based near 10 nm size MNPs and 1.5% agarose gel system. The decrease in specific absorption rate for agarose gel can be attributed to hindered Brownian movement of particles due to agarose gel.…”
Section: Resultssupporting
confidence: 85%
“…4 b). A similar 50% decrease in SAR was also reported by Makridis et al 18 and Shah et al 41 for ferrite-based near 10 nm size MNPs and 1.5% agarose gel system. The decrease in specific absorption rate for agarose gel can be attributed to hindered Brownian movement of particles due to agarose gel.…”
Section: Resultssupporting
confidence: 85%
“…Magnetic fluid hyperthermia (MFH) using magnetic nanoparticles as heat mediators has attracted interest for cancer therapy because of its noninvasiveness, localized therapeutic capability, and lack of therapeutic limits depending on the type of cancer. The heat generation capability of iron oxide, the most frequently employed heat generator platform, can be controlled by doping of other metals or varying the size or shape (Table S1). For example, the introduction of dopants such as Co, Mn, or Zn can increase the magnetic anisotropy, , leading to enhanced heat generation.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the Fe 3 O 4 nanocubes exhibited typical superparamagnetic behaviors (Figure S1A, Supporting Information), and the 18.4 nm Fe 3 O 4 nanocubes achieved higher saturation during a shorter field exposure time. Additionally, as different nanoparticle anisotropy would contribute to different heating capability, [ 12 ] this may explain why the 18.4 nm iNLMs showed the highest magnetothermal efficiency under AMF. Accordingly, the 18.4 nm iNLMs were selected for subsequent experiments.…”
Section: Figurementioning
confidence: 99%